Single interrupted vs. continuous all layer closure in bowel anastomosis in emergency surgeries: a comparative study - Kalokhe, Shifa A.; Sonawane, Rohit; Devdikar, Shrutik; Narshetty, G. S. (International Journal of Research in Medical Sciences, 2023)
Background: Intestinal anastomosis dates to ancient eras and hand sewn intestinal anastomosis is the most used technique worldwide. Various complications following bowel anastomoses are anastomotic leak resulting into peritonitis, abscess, fistula, necrosis, stricture. Various factors contribute to these complications including suturing technique. Leakage from the bowel anastomoses complication and accounts for about 1.3 to 7.7%, that is often associated with increased morbidity and mortality and prolonged stay. This comparative study endeavours to compare outcome of extra-mucosal interrupted single layer versus continuous all layers intestinal anastomosis in small and large bowel in terms of duration required to perform intestinal anastomosis, post-operative complications like anastomotic leak, duration of hospital stay in each group Aim of the present study was to compare time required to perform anastomosis and to compare the rate of postoperative complications and hospital duration. Methods: Based on detailed history, clinical examination and radiological investigations; patients were allotted in either group A or B. Group A: Bowel Anastomosis done by single layer (20 Patients) and Group B: Bowel anastomosis done by double layer (20 Patients). Time required to perform anastomosis and post op complications was assessed and compared. Results: In this prospective study of 40 patients, it was found that Group A required an average of 17 minutes and Group B required 24 minutes for anastomosis. The rate of postoperative complications were found to be similar in both groups. The mean hospital stay was also found to be similar. Conclusions: Thus, from this prospective comparative study, we conclude that both extra mucosal interrupted single layer and continuous all layer anastomosis have operative technical challenges and similar postoperative outcomes.